Lipid-nanoparticle-enabled nucleic acid therapeutics for liver disorders - Porkizhi Arjunan; Durga Kathirvelu; Gokulnath Mahalingam; Ashish Kumar Goel; Uday George Zacharaiah; Alok Srivastava; Srujan Marepally (Elsevier, 2024)
Inherited genetic disorders of the liver pose a significant public health burden. Liver transplantation is often limited by the availability of donor livers and the exorbitant costs of immunosuppressive therapy. To overcome these limitations, nucleic acid therapy provides a hopeful alternative that enables gene repair, gene supplementation, and gene silencing with suitable vectors. Though viral vectors are the most efficient and preferred for gene therapy, pre-existing immunity debilitating immune responses limit their use. As a potential alternative, lipid nanoparticle-mediated vectors are being explored to deliver multiple nucleic acid forms, including pDNA, mRNA, siRNA, and proteins. Herein, we discuss the broader applications of lipid nanoparticles, from protein replacement therapy to restoring the disease mechanism through nucleic acid delivery and gene editing, as well as multiple preclinical and clinical studies as a potential alternative to liver transplantation.